Senior Citizens Protesting at Exhibit Hall Mayor Dan Whitehurst Funding Policies - Watkins, Howard::::::::: (1981)
Senior Citizens carrying hand painted signs: "We Voted You In, We Can Vote You Out" "I'm Too Old to Drive, Give Me My Bus"